Proceedings First Asian Test Symposium (ATS `92)
DOI: 10.1109/ats.1992.224436
|View full text |Cite
|
Sign up to set email alerts
|

Test input vectors for supply current testing of TTL combinational circuits

Abstract: In this paper, test input vectors for ISCAS-85 benchmark circuits are derived, with which single faults of each signal line in the lTL combinational circuits can be detected by their quiescent supply currents. Also, they are compared with the vectors for fault detection methods based on the primary output logic values. It is shown that by detecting faults with supply currents of T7z circuits, smaller size of test inputs can be derived for most of the circuits than fault detection methods based on the primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It is found that open-circuit faults are very difficult to be detected from the test generation results in [6] and [7]. In order to examine the worst-case testability of our supply current testing, single open-circuit faults are attempted to be detected.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that open-circuit faults are very difficult to be detected from the test generation results in [6] and [7]. In order to examine the worst-case testability of our supply current testing, single open-circuit faults are attempted to be detected.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…In the past, we proposed a random test generation algorithm [6] and a deterministic one [7]. The algorithms can be used for generating test input vectors, only by changing the criterion for judging whether 7;.…”
Section: Test Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the distributions of the unfaulty circuit and a circuit having an open fault, it is determined whether an input vector can be selected as a test vector. In the past, we proposed a random test generation algorithm [4] and a deterministic one [5] for the supply current tests. In our experiments, test input vectors are derived by a modified random test input generation method, which is almost the same as in [6].…”
Section: Testability Analysismentioning
confidence: 99%
“…The method is to detect faults by measuring the quiescent supply current of a circuit under test and comparing it with one of the unfaulty circuit. Also, we proposed a fast random test input generation method for the supply current tests and an algorithmic one in [4] and [5], respectively.…”
Section: Introductionmentioning
confidence: 99%